Filipino beta zero thalassaemia: a high Hb A2 beta zero thalassaemia resulting from a large deletion of the 5' beta globin gene region. Issue 3 (March 1993) - Motum, P I; Kearney, A; Hamilton, T J; Trent, R J
Abstract : A large novel deletional beta zero thalassaemia mutation associated with unusually high levels of haemoglobin (Hb) A2 in heterozygotes is described in two unrelated subjects of Filipino background. The deletion was characterised by DNA mapping including pulsed field gel electrophoresis. Filipino beta zero thalassaemia extends for approximately 45 kb beginning approximately 1.5 kb 3' to the delta globin gene. It is the largest deletion to date which gives rise to the beta zero thalassaemia phenotype. This mutation, similar to previously described deletional beta zero thalassaemias associated with high Hb A2, removes sequences 5' to the beta globin gene promoter and emphasises the functional importance of the 5' beta globin region in eliciting the unusually high level of Hb A2. This example also suggests that it is the 3' sequences which are transposed rather than the actual deletion size which are significant in the raised fetal haemoglobin (Hb F) found with some of the thalassaemias.